Incentive-compatible mechanisms for norm monitoring in open multi-agent systems (Extended abstract) - Alechina, Natasha; Halpern, Joseph Y.; Kash, Ian A.; Logan, Brian (2018)
We consider the problem of detecting norm violations in open multi-agent systems (MAS). In this extended abstract, we outline the approach of [Alechina et al., 2018], and show how, using ideas from scrip systems, we can design mechanisms where the agents comprising the MAS are incen-tivised to monitor the actions of other agents for norm violations